Sirt1 increases skeletal muscle precursor cell proliferation - Rathbone, Christopher R. (2008)
It is important to understand the mechanisms that control muscle precursor cell (MPC) proliferation for the development of countermeasures to offset the deleterious effects of the aging-related loss of skeletal muscle mass (and myonuclei) and the impaired ability of old muscle to regrow and regenerate. Over-expression of the NAD(+)-dependent histone deacetylase Sirt1 increased MPC proliferation and cell cycle progression as evidenced by increased 5-bromo-2′-deoxyuridine (BrdU) incorporation, an increase in cell number, proliferating cell nuclear antigen expression, and the phosphorylation of retinoblastoma protein. Associated with Sirt1-mediated increase in MPC cycle progression were the bidirectional decreases and increases in the expression of the cyclin-dependent kinase inhibitors p21(Waf/Cip1) and p27(Kip1), respectively. Based upon our recent observation that lowering oxygen (O(2)) in culture from ambient (20%) to estimated physiological levels (5%) increased MPC proliferation, we next measured Sirt1 protein at 5% and 20% O(2). Interestingly, in addition to increased proliferation in MPCs cultured at 5% O(2), Sirt1 expression increased, compared to 20% O(2). Using O(2) levels as a platform to modulate basal Sirt1 protein, activation of Sirt1 activity with resveratrol in 20% O(2) increased MPC proliferation while inhibition of Sirt1 with nicotinamide in 5% O(2) lowered proliferation. For the first time, Sirt1 has been shown to increase MPC proliferation. These findings could have clinical significance since MPC proliferation has important implications in regulating skeletal muscle growth, maintenance, and repair, and the aging-related loss of skeletal muscle mass.